Information technology strategic plan for small and medium-sized enterprises - Pincay Ponce, Jorge Iván (2015)
With the objective of strengthening planning procedures and support services concerned with information and communication technologies in small and medium-sized enterprises, and in view of the lack of this type of plans, we propose a model for the strategic planning of technologies used by organizations, aimed to reduce financial, social, technical, operational, legal and human risks. We considered the background literature on the following methodologies: (A) Enterprise System Planning using a Strategic Approach IBM (BSP/SA), (B) Applied Strategic Planning, and (C) Strategic Information Technology Planning. This theoretical background was combined with data from a non-probabilistic national sample through expert selection of 150 enterprises, and via an on-line questionnaire detailing components, principles, values, standards, metrics, phases and temporal horizon of the methodology used for model implementation. The chosen business segment shows peculiarities that implicate continuous identification of resource and ability dimensions of an enterprise and contextual requirements. These data, used by technology experts, are the ingredient to formulate a technological plan, adjusted to priorities of small and medium-sized enterprises.